Matrix-assisted laser desorption/ionization imaging mass spectrometry for the spatial location of feline oviductal proteins - Apparicio, M.; Santos, V. G.; Rocha, D. F.O.; Ferreira, C. R.; Macente, B. I. [UNESP]; Magalhães, G. M.; Alves, A. E. [UNESP]; Motheo, T. F. [UNESP]; Padilha-Nakaghi, L. C. [UNESP]; Pires-Buttler, E. A. [UNESP]; Luvoni, G. C.; Eberlin, M. N.; et al. (Wiley, 2017)
With the purpose of identifying factors involved in early stages of embryo development in the domestic cat, matrix-assisted laser desorption/ionization imaging mass spectrometry (MALDI-IMS) was used for the first time to describe the spatial localization of proteins in the oviducts of queens. Oviducts were obtained from two 2 and 4 years old cross-bred queens, divided into three segments, snap-frozen in liquid nitrogen and then stored at −80°C until use. Next, they were sectioned in a cryostat, fixed on ITO (indium tin oxide) conductive glass slides for MALDI-IMS and serial sections were collected on microscope slides for histology. As confirmed by histology, MALDI-IMS was able to show contrasting protein distributions in the oviductal infundibulum, ampulla and isthmus. Mass spectra were characterized by abundant ions of m/z 1,259, 4,939, 4,960 and 10,626, which have been tentatively attributed to keratin, thymosin β10, thymosin β4 and S100, respectively. Keratin and thymosins are involved in the biological response to tissue damage. S100 proteins are calcium-modulated proteins implicated in a variety of cellular activities, including cell differentiation and regulation of cell motility. These results suggest that protein composition differs between segments of the cat oviduct, which corresponds to morphological changes within these sections. Further functional studies could elucidate the effects of these proteins on feline reproductive physiology.
Keywords: cat; matrix-assisted laser desorption/ionization imaging mass spectrometry; protein; reproduction; uterine tube